RHETORICAL MOVE AND GENRE KNOWLEDGE DEVELOPMENT IN LOCAL AND INTERNATIONAL GRADUATES’ THESIS AND DISSERTATION ABSTRACTS - Putri, Tara Devina; Kurniawan, Eri (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
In recent years, there has been an increasing interest in the study of research abstracts and its rhetorical structure. While the number of studies in rhetorical moves of RA abstracts are growing, there is still little attention given to thesis and dissertation abstracts especially in relation to the link between genre knowledge and its rhetorical realization. The present study aims to identify the variations of rhetorical move manifestation in abstracts of master’s theses and dissertations written by local and international graduate lecturers and explore the relationship between the manifestations and the author’s genre knowledge development. This study employed a qualitative approach with Hyland’s (2000) five-move analysis model as the main framework of the study. The findings revealed that there were similarities in the rhetorical structure of abstracts by the local and international graduates. The study also found that educational level and supportive academic environment play an important role in author’s genre knowledge trajectories. The findings discovered in the study provide a clearer picture to help in the development of a universal guideline for abstract writing in final papers for higher education.